Senior High School Heads’ Perception on Predominant Forms of Continuous Professional Development in Ghana - , Abraham Gyamfi; , Patience Langee; , Abraham Yeboah (Archives of Current Research International, 2023)
The purpose of the study was to find out the predominant forms of Continuous Professional Development for senior high school heads of public Senior High School/ Technical and Vocational Educational and Training (SHS/TVET) in Greater Accra Region of Ghana and their perception of Continuous Professional Development. A descriptive survey method was used, where a questionnaire was administered to the Heads (Headmaster, Assistant Head-Administration and Assistant Head-Academic) of SHS/TVET in the Greater Accra Region. The accessible population for this study comprised all heads of SHS/TVET in the Greater Accra Region. The target population consisted of all heads of public all SHS/TVET in the Greater Accra Region. A census was used to select all heads of public all SHS/TVET in the Greater Accra Region. A self-designed questionnaire with a Cronbach alpha reliability coefficient of 0.85 was used for the data collection. Means and Standard Deviations were used to analyse data for the study. It was found that Conferences, workshops and academic programs are the predominant form CPD undertaken by the heads of public SHS/TVET and that the heads expressed that the performance of the Head is dependent on the perception of professional development. It was therefore recommended that the Ministry of Education to make policies as to enhancing sponsorships continuous Professional Development for senior high school heads in the management of the SHS/TVET.